2021
DOI: 10.3389/fphar.2021.607572
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Activity of Racemic and Dextrorotatory Forms of Thioctic (Alpha-Lipoic) Acid in Low Back Pain: Preclinical Results and Clinical Evidences From an Open Randomized Trial

Abstract: Peripheral neuropathies, characterized by altered nociceptive and muscular functions, are related to oxidative stress. Thioctic acid is a natural antioxidant existing as two optical isomers, but most clinically used as racemic mixture. The present study investigated the central nervous system’s changes which followed loose-ligation-derived compression of sciatic nerve, the putative neuroprotective role of thioctic acid and the pain-alleviating effect on low-back pain suffering patients. Loose ligation of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
1
8
0
2
Order By: Relevance
“…Compounds were solubilized in NaOHsupplemented physiologic solution and buffered to 7.4 pH by adding HCl. Different racemic and lipoic acid salt compounds were solubilized in saline [25] and SHR rats were treated once a day for 30 days with an i.p. injection of 250 µmol/kg/day of (+/-)-ALA (n = 6); 125 µmol/kg/day of (+/-)-ALA (n = 6); 125 µmol/kg/day of (+)-ALA (n = 6) and 125 µmol/kg/day of (-)-ALA (n = 6).…”
Section: Animals and Tissue Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds were solubilized in NaOHsupplemented physiologic solution and buffered to 7.4 pH by adding HCl. Different racemic and lipoic acid salt compounds were solubilized in saline [25] and SHR rats were treated once a day for 30 days with an i.p. injection of 250 µmol/kg/day of (+/-)-ALA (n = 6); 125 µmol/kg/day of (+/-)-ALA (n = 6); 125 µmol/kg/day of (+)-ALA (n = 6) and 125 µmol/kg/day of (-)-ALA (n = 6).…”
Section: Animals and Tissue Treatmentmentioning
confidence: 99%
“…4354-MC-050) diluted 1:250. This mouse monoclonal antibody specifically binds to 8-oxo-dG within DNA, as detailed [25]. The product of the immune reaction was then revealed by exposing slides with anti-mouse biotinylated polyclonal antibody (Merck-Millipore, Burlington, MA, USA, Cat.…”
Section: Histological Analysis Immunohistochemistry and Immunofluores...mentioning
confidence: 99%
See 1 more Smart Citation
“…Огляд літератури /Literature Review/ попереку [3]. До дослідження було залучено 100 пацієнтів з радикулопатією нижніх кінцівок (однобічною або двобічною), яких було розподілено на дві групи по 50 осіб у кожній.…”
Section: ключові слова: R(+)-енантіомер α-ліпоєвої кислоти; патологічні стани; аналізunclassified
“…In a dose/response curve model of R-LA and S-LA in the working rat heart during reoxygenation, the R-enantiomer was found to be more superior in the enhancement of the aortic flow [ 19 ]. Moreover, in a model of sciatic nerve injury in hypertensive rats, R-LA was more active than S-LA in terms of analgesic and neuroprotective efficacy [ 20 , 21 ]. This may be related to the better recognized dextrorotatory enantiomer by enzymes, as it was found that the maximum plasma concentration (Cmax) is approximately 40–50% higher with R-LA than with S-LA at the same dose [ 11 ].…”
Section: Introductionmentioning
confidence: 99%